PERAN ASPEK TEHNOLOGI PERTANIAN KELAPA SAWIT UNTUK MENINGKATKAN PRODUKTIVITAS PRODUKSI KELAPA SAWIT - rosmegawati rosmegawati (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2021)
Abstract Oil palm farming is an economic activity that is very important for economic growth because the productivity of oil palm agriculture can increase the country's Gross Domestic Product (GDP).This paper describes the technological efforts used to increase the productivity of oil palm agriculture, through the selection and processing of the right technology.The agricultural technology proposed in this paper is the technology of fertilization, seeding, handling of plant diseases, and handling of plant development and in the future it is recommended to digitize oil palm plants. Keywords: Technology, Productivity, Palm Oil